(untitled) (Contemporary Mathematics, 2025)
This paper is devoted to the study of a class of commutative non-associative algebras characterized by the identity: where α ∈ [0, 1]. In this study, we strongly use the Peirce decomposition technique. This allowed us to determine the conditions for an algebra of this class to be Bernstein, principal train, or evolution.